Synthesis and optimization of micro-sized bacterial-based violet pigment using response surface methodology - Mohd. Yatim, Haryani (2017)
Violet pigments, extracted from a bacteria known as Chromobacterium violaceum, has raised the enthusiasm of researchers in conducting comprehensive studies on these pigments due to their diverse biological activities include antibacterial and antioxidant properties. There is, however, a limitation related with the solubility of the violet pigment, by which it is commonly dissolved in toxic solvents such as dimethyl sulfoxide (DMSO) and methanol instead of being soluble in biological fluids and water. This approach did not synchronized with the public demands for products that are both eco-friendly and safe towards the environment and human body. Hence, this study provides a method to synthesise the violet pigment in microscale through an encapsulation technique using chitosan-tripolyphosphate (TPP) microparticles. Owing to the exceptional properties of high surface to volume ratio of microparticles, the solubility of the violet pigment in water and biological fluid could be improved. The synthesis of microparticles in this study involved ionic gelation between chitosan and TPP, in which several parameters were taken into consideration in order to control the dispersion stability of the violet pigment in the suspension. It is well known that particles in microscale will tend to aggregate, thus causing diminution of their biological activities. Therefore, preparation parameters, including the concentration of chitosan, tripolyphosphate (TPP) and pigment as well as the mass ratio of chitosan to TPP, were optimized using Response Surface Methodology (RSM). The aim was to obtain small particles size down to microscale with low range of polydispersity index (PDI) and high zeta potential. Minimum particle size of 149.0 nm with polydispersity index of 0.367 and zeta potential of +23.40 mV was obtained at the optimal formulations of 2.33 mg/mL of Cs, 1.5 mg/mL of TPP and 1 ppm of violet pigment and at mass ratio of chitosan:TPP of 7:1